Exploration and Identification of Amorphophallus spp in South Sulawesi - Nurhaya J Panga; Hajar Hajar; Rinaldi Sjahril; Rusdayani Amin (Musamus University, 2019)
To support the development of Amorphophallus as potential economic commodity especially in South Sulawesi, the first step that can be taken is to inventory the species found in this region. In this study we explore and identify Amorphopallus species found in South Sulawesi. The area of exploration was choose based on the information collected from media and personal interview about the plant with student that came from across the South Sulawesi Province. Exploration was conducted by driving a car and hicking through provincial and district oth habitat for Amorphophallus according to literature. We also gather information by showing pictures on the plant to the resident or farmers around the exploration site. We then collected the plant that found in the exploration, and identified each of them by morphological characters. This research found three species Amorphophallus, namely A. paeonifolius, A. variabilis, and A. muelleri spread across the South Sulawesi Regency, in 11 spot location at eight district: Takalar, Jeneponto, Bantaeng, Gowa, Maros, Bone, Soppeng, and East Luwu. The habitat were the plant grow naturally are under tree canopy, or other shade, which indicate the potensial of this plant to growth under agroforestry system.